A high-toughness ultra-high-strength martensitic stainless steel material and its preparation method and application

By optimizing the composition ratio of elements in the Fe\Ni\Cr\Co\Mo system and adding Nb elements, combined with the control of aging treatment temperature, a high-tough ultra-high strength martensitic stainless steel material was prepared, which solved the problem of difficult to take into account both yield strength and elongation in the prior art, and achieved material properties with yield strength greater than 2000MPa and elongation greater than 5%, meeting the needs of the "3C" application field.

CN118109759BActive Publication Date: 2025-05-02HUIJIN ATOMIZING SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311026030.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-05-02
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

The existing metal injection molded ultra-high strength steel materials are difficult to balance between yield strength and elongation, and cannot provide materials with yield strength greater than 2000MPa and elongation greater than 5%, which cannot meet the demand for high toughness and high strength in the application field of "3C".

Method used

By optimizing the composition ratio of elements in the Fe\Ni\Cr\Co\Mo system, adding Nb elements, and controlling the temperature conditions of the aging treatment, a high-tough ultra-high strength martensitic stainless steel material was prepared. Its chemical composition includes Cr 7.0~9.0wt%, Ni 7.1~9.0wt%, Co 9.0~14.0wt%, Mo 5.5~7.0wt%, Nb 0.05~0.5wt%, C ≤0.03wt%, and the balance is Fe.

Benefits of technology

The yield strength is greater than 1900MPa, especially greater than 2000MPa, and the elongation is greater than 5%, which improves the toughness and drop resistance of the material, and meets the demand for high-strength and high-toughness materials in the application field of "3C".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118109759B_ABST
    Figure CN118109759B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of powder metallurgy materials and intelligent manufacturing technology, and relates to a high-toughness ultra-high-strength martensitic stainless steel material and its preparation method and application. The material is composed of the following chemical elements: Cr 7.0~9.0wt%, Ni 7.1~9.0wt%, Co 9.0~14.0wt%, Mo 5.5~7.0wt%, Nb 0.05~0.5wt%, C≤0.03wt%, the balance is Fe, and inevitable impurity elements. The material of the present invention is combined with the injection molding process, so that the yield strength of the martensitic stainless steel reaches more than 1900 MPa, and the elongation is greater than 5%, especially the yield strength is greater than 2000 MPa and the elongation is greater than 5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of powder metallurgy materials and intelligent manufacturing, and relates to a metal material, and in particular to a high-toughness and ultra-high-strength martensitic stainless steel material, and a preparation method and application thereof. Background Art

[0002] Metal Injection Molding (MIM) is a new type of powder metallurgy near-net molding technology derived from the powder metallurgy and plastic injection molding industries. In recent years, this technology has been developed to maximize the content of solid particles and completely remove the binder and densify the molded blank during the subsequent sintering process. The basic process steps of metal injection molding are: first, select metal powder and binder that meet the requirements of MIM, then use appropriate methods to mix the powder and binder into a uniform feed at a certain temperature, granulate it, and then inject it into the molded blank. After degreasing, sinter it to densify it into the final product.

[0003] MIM can produce metal parts with complex shapes, including small internal structures, thin-walled structures and precision holes, and can achieve highly precise forming with excellent dimensional control and surface quality. Therefore, MIM has been widely used in the manufacture of some parts with high precision requirements.

[0004] In the "3C" application field, especially in the field of folding screen mobile phones and computers, in order to achieve lightweight wearable devices, high-strength martensitic steel and ultra-high-strength steel have begun to apply folding screen shaft design. Due to the complex structure of this component, it is generally designed and manufactured by metal injection molding, but the sintering density of injection molded sintered parts can generally only reach 96%~99.5% of the theoretical density, which cannot reach the density of casting materials, and it is impossible to further improve the material properties by hot and cold deformation (calendering, forging) methods. Therefore, the ultra-high-strength steel material produced by injection molding, even if it is a sintered material with excellent sintering, has a porosity of 0.5~3% in its sintered matrix. The porosity of this material can be reduced to near zero by hot isostatic pressing, and the density can be increased to near the theoretical density. However, this method greatly increases the processing cost and is difficult to achieve low-cost large-scale mass production.

[0005] At present, many patents on injection molded ultra-high strength steel generally only focus on the yield strength of the material, while its elongation is far from enough attention in material development. This kind of void in the matrix of injection molded sintered materials is itself a defect of the material. Compared with materials with a density of 100% such as casting and forging, its performance such as strength and elongation is greatly reduced, especially the elongation of the material. In practical applications, even for materials with an elongation of 5%, due to the presence of sintering voids, the material is still likely to fracture brittlely, and the material cannot pass the drop test. For example, for a material with a yield strength of 1500MPa, the impact value of a material with an elongation of 5% and a material with an elongation of 8% is only 8J / cm 2 , while the latter can reach 40J / cm 2 In the tensile fracture test, the former is close to brittle fracture, while the latter is generally a plastic fracture with a diameter-shrinking dimple.

[0006] Therefore, "3C" applications often require ultra-high strength steel materials with higher elongation and better toughness to improve the application reliability of the materials and meet the requirements of a wide range of applications.

[0007] However, due to the multi-void characteristics of the injection molded sintered material matrix, this common material defect makes it very difficult to improve the elongation and toughness of injection molded ultra-high strength steel. When the material elongation is based on 6%, it becomes very difficult to further improve the elongation performance.

[0008] In the prior art, the injection molding materials are described as follows.

[0009] CN103981436A discloses a high-strength maraging steel for metal powder injection molding and a manufacturing method thereof. The maraging steel comprises, by weight percentage, 17-19% Ni, 8-10% Co, 4.5-6.5% Mo, ≤0.08% C, and the remainder is iron and unavoidable impurities. The tensile strength of the material reaches more than 1500MPa, the elongation reaches more than 10%, and the impact strength reaches 50J / cm 2 Above, the hardness of the material is HRC40-48.

[0010] The low-cobalt martensitic stainless steel powder disclosed in CN114480943A has the following chemical composition by mass percentage: Ni: 9-13%, Mo: 9-13%, Co: 4-8%, Ti: 1.5-2.5%, Al: 1-2%, Nb: 0.2-0.5%, Mn: <1%, C: ≤0.03%, O: ≤0.03%, Fe: balance. The tensile strength is about 2050MPa and the elongation is about 5%.

[0011] CN111250694A discloses an injection molding method for high-strength and high-toughness metal parts. The specific metal elements and mass percentages of the alloy powder used are: nickel, 17% to 18%; cobalt, 8.5% to 9.5%; molybdenum, 4.5% to 5.0%; and the balance is iron. The high-strength and high-toughness rotating shaft parts obtained by using the alloy powder have a yield strength of 1350MPa and an elongation of 6%.

[0012] CN115740427A discloses a MIM powder of 1800MPa ultra-high strength and high toughness steel, comprising the following metal powders in weight percentage: C 0.0-0.6%, Cr 2.0-3.5%, Ni 11.0-14.0%, Co 14.0-17.0% and Mo 1.5-2.5%, and the particle size of the MIM powder is ≤50μm. By improving the raw material composition and the hot degreasing and sintering process, an ultra-high strength and high toughness steel part with a yield strength of ≥1800MPa, an elongation of ≥5%, and a hardness of 52-58HRC is prepared.

[0013] WO2023025252A1 discloses steel, steel structure, electronic equipment and method for preparing steel structure, wherein the steel includes Fe, with a weight percentage of >60.67wt%; Cr, with a weight percentage of 8.01wt%~8.99wt%; Ni, with a weight percentage of 6wt%~7wt%; Co, with a weight percentage of 15.01wt%~15.99wt%; Mo, with a weight percentage of 5.5wt%~6.5wt%; Nb, with a weight percentage of ≤0.5wt%; O, with a weight percentage of ≤03wt%; and C, with a weight percentage of <0.05wt%. The steel structure made of the steel with this component has a yield strength of about 1900MPa and an elongation of 4-6%.

[0014] It can be seen from the above-listed prior arts that for metal injection molding materials, strength and elongation are important properties that are generally concerned. Generally, the strength of steel products is inversely related to their elongation. In practical applications, steel products usually need to have certain strength and elongation at the same time to meet different requirements. The prior art cannot provide high-toughness metal injection molding materials with a yield strength greater than 2000MPa and an elongation greater than 5%. In the "3C" application field, steel structures with this performance are urgently needed. Summary of the invention

[0015] The purpose of the present invention is to supplement the metal injection molding materials in the prior art and provide a metal injection molding material with a yield strength greater than 1900 MPa, especially a yield strength greater than 2000 MPa, and an elongation greater than 5%.

[0016] A first aspect of the present invention provides a high-toughness and ultra-high-strength martensitic stainless steel material.

[0017] The technical solution adopted by the first aspect of the present invention to solve the technical problem is:

[0018] A high-toughness, ultra-high-strength martensitic stainless steel material composed of the following chemical elements:

[0019] Cr 7.0~9.0wt%, Ni 7.1~9.0wt%, Co 9.0~14.0wt%, Mo 5.5~7.0wt%, Nb 0.05~0.5wt%, C≤0.03wt%, the balance is Fe, and inevitable impurity elements.

[0020] The Cr element mainly provides stainless steel with corrosion resistance. Chromium forms a stable chromium oxide layer with oxygen, which can prevent the stainless steel surface from reacting with oxygen and water in the environment, thereby protecting the stainless steel from corrosion. Chromium is also a ferritizing element in the material, and too high a chromium content will reduce the strength of the material.

[0021] Ni is also a toughening element in ultra-high strength stainless steel, which improves the fracture resistance of martensitic steel, increases the plasticity and toughness of the material, and can improve the passivation tendency of stainless steel and improve the corrosion resistance of martensitic stainless steel. However, nickel has a greater tendency to austenitize, and too much nickel makes it difficult for the material to form martensitic structure, reducing the mechanical properties.

[0022] As an important strengthening element, the Co element promotes the formation of dispersed precipitate phases during the aging process of the material. The increase of Co is beneficial to improving the toughness and strength of the material within a certain range. An appropriately high Co content will increase the martensitic transformation temperature of the material, making it easier to achieve martensitic transformation during the gas quenching process after solution heat treatment, which is beneficial to improving the performance and stability of the material. However, as a practical demand for this kind of martensitic stainless steel with good toughness, the material needs to retain an appropriate residual austenite phase on the basis of the martensitic matrix in order to truly make the material have toughness and ductility on the basis of high strength. Excessive Co content not only promotes the formation of dispersed phase brittleness in a transitional manner, but also prompts the residual austenite to fully transform into martensite, which ultimately makes the material brittle. Therefore, from the technical characteristics, too high Co content is detrimental to the toughness of the material. Too high Co content will also increase the cost of materials.

[0023] Mo is the most important solid solution strengthening element in martensitic stainless steel. Its solid solution strengthening effect can improve the yield strength and tensile strength of martensitic stainless steel, but too high Mo will form a brittle phase in the material. While increasing the strength, the toughness of the material is greatly reduced until it evolves into a brittle material.

[0024] In general, Fe\Ni\Cr\Co\Mo series ultra-high strength martensitic stainless steel is an element substitution solid solution type ultra-high strength stainless steel. Mo is the reinforcement core, forming a reinforcement material with (Fe / Cr / Ni / Co)Mo as the basic solid solution structure. The strength and toughness of the material are determined by factors such as the element composition ratio, phase structure, grain size, dislocation density, and material defects in the material.

[0025] The present invention also adds Nb to the Fe\Ni\Cr\Co\Mo system. The addition of Nb is generally believed to improve the strength of the material, but the addition of excessive Nb will reduce the toughness of the material. In this technical solution, 0.05~0.5wt% of Nb is added, and the raw material composition and its content are adjusted and improved to optimize the most suitable composition, combined with the injection molding process, so that the yield strength of the martensitic stainless steel reaches more than 1900 MPa, and the elongation is greater than 5%, especially the yield strength is greater than 2000MPa and the elongation is greater than 5%.

[0026] The martensitic stainless steel material of the present invention can also achieve the selection of different strength and toughness ranges by controlling the temperature conditions of the aging treatment. For example, when the aging temperature range is controlled at 520-535°C, the material yield strength that can be obtained is 1900-2100MPa, and the elongation is more than 5%. When the aging temperature range is 540-560°C for 4-6 hours of vacuum aging, the material yield strength that can be obtained is 1600-1800MPa, and the elongation is more than 8%. According to actual use requirements, the preparation of ultra-high strength or ultra-high toughness performance materials is selected, which further broadens the scope of use of the material.

[0027] In one embodiment of the present invention, the mass percentage content of Cr, Ni, Co, Mo, and Nb elements is: Cr 7.0-9.0wt%, Ni 7.5-8.0wt%, Co 9.5-14.0wt%, Mo 5.8-6.5wt%, Nb 0.15-0.4wt%. In particular, when the Ni content is between 7.5-8.0wt%, the material has a yield strength greater than 2000 MPa and an elongation greater than 5%.

[0028] In one embodiment of the present invention, the mass percentage contents of Cr, Ni, Co and Mo elements are: Cr 8.0-9.0wt%, Ni 7.5-8.0wt%, Co 9.5-14.0wt%, Mo 5.8-6.5wt%, and Nb 0.2-0.4wt%.

[0029] In one embodiment of the present invention, the mass percentage contents of Cr, Ni, Co and Mo elements are: Cr 8.0-9.0wt%, Ni 7.5-7.8.0wt%, Co 10.0-13.0wt%, Mo 6.0-6.5wt%, and Nb 0.2-0.35wt%.

[0030] A second aspect of the present invention provides a steel structure, which is formed by a metal injection molding process using the high-toughness and high-strength stainless steel raw material mentioned above.

[0031] The above steel structure has a yield strength of 1900MPa to 2100MPa and an elongation of more than 5%, or a yield strength of more than 1600MPa to 1800MPa and an elongation of more than 8%, especially 8% to 9%.

[0032] A third aspect of the present invention provides a method for preparing a steel structure, comprising the following steps:

[0033] S1: high-toughness and high-strength stainless steel powder raw material with a particle size D90 less than 40 microns is mixed with a binder such as POM to obtain a feed particle raw material; the high-toughness and high-strength stainless steel raw material is composed of the following chemical elements: Cr 7.0~9.0wt%, Ni 7.1~9.0wt%, Co 9.0~14.0wt%, Mo 5.5~7.0wt%, C≤0.03wt%, Nb 0.05~0.5wt%, the balance is Fe, and inevitable impurity elements;

[0034] S2: injection molding the granular raw material into a green body;

[0035] S3: catalytically debinding the green body;

[0036] S4: After catalytic debinding, the green body is subjected to thermal debinding and sintering in a negative pressure environment to obtain a sintered part. The sintering temperature ranges from 1360 to 1380°C.

[0037] S5: The sintered part is subjected to solution treatment and vacuum aging treatment in sequence to obtain the steel structure part.

[0038] In one embodiment of the present invention, in step S5, the vacuum aging treatment operation is: aging treatment at 520-535° C., keeping warm for 4-6 hours; or aging treatment at 540-560° C., keeping warm for 4-6 hours.

[0039] In one embodiment of the present invention, in step S1, the granulation temperature is 175-200°C.

[0040] In one embodiment of the present invention, in step S5, the solution treatment operation is: heating the temperature to 1040-1085°C at a heating rate of 5-10°C / min in a vacuum environment, keeping the temperature for 60-120 minutes, and then quenching to room temperature with high-pressure gas.

[0041] In one embodiment of the present invention, in step S5, 6 atm to 10 atm high pressure inert gas is used for gas quenching to room temperature. The inert gas is nitrogen or argon.

[0042] In one embodiment of the present invention, in step S3, nitric acid or oxalic acid is used to perform catalytic degreasing on the green body; the temperature condition for nitric acid degreasing is 110°C±5°C, and the temperature condition for oxalic acid degreasing is 130°C±5°C.

[0043] A fourth aspect of the present invention provides a steel structure member manufactured using the above-mentioned preparation method.

[0044] In one embodiment of the present invention, the yield strength of the steel structure is between 1900 MPa and 2100 MPa, and the elongation can reach more than 5%. Or the yield strength is greater than 1600 MPa to 1800 MPa, and the elongation can reach more than 8%, especially 8%-9%.

[0045] The fifth aspect of the present invention provides applications of the above-mentioned high-toughness and high-strength stainless steel raw materials and the above-mentioned steel structural parts in 3C products, automotive products, aviation products, and medical products.

[0046] In particular, the application of the above-mentioned high-toughness and high-strength stainless steel raw materials and the above-mentioned steel structural parts in the manufacturing of 3C products and their components.

[0047] The "3C products" mentioned in the present invention are a general term for computer, communication and consumer electronic products, also known as "information appliances". For example, computers, tablet computers, mobile phones or digital audio players, etc. These products have complex structures, high precision requirements, high strength and toughness requirements, and the stainless steel of the present invention is particularly suitable for products in these fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a tensile curve diagram of the steel structure member provided by Example 9 according to Example 3 of the present invention.

[0049] Figure 2 This is a tensile curve diagram of the steel structure provided by Example 10 according to Example 3 of the present invention.

[0050] Figure 3This is a backscattered electron diffraction (EBSD) phase test diagram of a steel structure provided by Example 3 of the present invention in a scanning electron microscope. The lower half is a partial enlargement of the upper half. The figure shows that a certain proportion of residual austenite is contained on the basis of the martensite matrix material.

[0051] Figure 4 , the backscattered electron diffraction (EBSD) phase test diagram of the steel structure provided in the scanning electron microscope of the comparative example 1 of the present invention. The lower half is a partial enlargement of the upper half. The figure shows that the material is basically martensite structure, with little residual austenite structure. DETAILED DESCRIPTION

[0052] The technical scheme of the present invention is further described in detail below through specific examples. It should be understood that the implementation of the present invention is not limited to the following examples, and any formal modifications and / or changes made to the present invention will fall within the scope of protection of the present invention. The parameter ranges involved include endpoint values ​​unless otherwise specified.

[0053] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0054] The structural components of "3C" products are generally small precision parts with complex three-dimensional structures. They are responsible for the smooth operation of the mechanism and the reliability of the structure. Therefore, the requirements for materials are multi-dimensional. The preparation process is required to facilitate the molding of precise and complex structures to provide greater freedom in structural design. There are also high requirements for the strength (such as yield strength, tensile strength) and toughness (such as elongation) of the material.

[0055] In this specific embodiment, a stainless steel material with higher strength and better toughness is provided for use in injection molding to form a steel structure. The yield strength of the formed steel structure is greater than 1900 MPa and the elongation is greater than 7%.

[0056] Testing methods for tensile strength, yield strength and elongation: The materials are injected and sintered into mechanical tensile test specimens, and tested according to the national metal material tensile test standard GB / T228.1-2010. The diameter of the sintered specimen is Ф3.20±0.05, and the standard length of the specimen is 25mm; the elongation is calculated by measuring the length after breaking; the tensile strength and yield strength are collected by the microcomputer of the testing machine.

[0057] The core of the present invention is to provide a high-toughness and high-strength stainless steel raw material composed of the following chemical elements:

[0058] Cr 7.0~9.0wt%, Ni 7.1~9.0wt%, Co 9.0~14.0wt%, Mo 5.5~7.0wt%, Nb 0.05~0.5wt%, C≤0.03wt%, the balance is Fe, and inevitable impurity elements. Inevitable impurity elements such as Mn, Si, P, S and other elements.

[0059] In some embodiments, the mass percentage contents of Cr, Ni, Co, Mo, and Nb elements are: Cr 7.0-9.0wt%, Ni 7.5-8.0wt%, Co 9.5-14.0wt%, Mo 5.8-6.5wt%, and Nb 0.15-0.4wt%.

[0060] In some embodiments, the mass percentage contents of Cr, Ni, Co, and Mo elements are: Cr 8.0-9.0wt%, Ni 7.5-8.0wt%, Co 9.5-14.0wt%, Mo 5.8-6.5wt%, and Nb 0.2-0.4wt%.

[0061] In some embodiments, the mass percentage content of Cr, Ni, Co, and Mo elements is: Cr 8.0-9.0wt%, Ni 7.5-8.0wt%, Co 10.0-13.0wt%, Mo 6.0-6.5wt%, and Nb 0.2-0.35wt%. The above high-toughness and high-strength stainless steel raw material is used to prepare a steel structure of a specific structure through a metal injection molding process, and the method is as follows:

[0062] (1) Raw materials preparation:

[0063] Prepare stainless steel raw materials and binders. The stainless steel raw materials adopt the above-mentioned high-toughness and high-strength stainless steel raw materials, including Cr 7.0~9.0wt%, Ni 7.0~9.0wt%, Co 9.0~15.0wt%, Mo5.5~7.0wt%, Nb 0.05~0.5wt%, C≤0.03wt%, the balance is Fe, and inevitable impurity elements. The stainless steel raw materials can be in the form of pre-alloyed powder or pure metal powder. The powder raw materials can be prepared by atomization, reduction, mechanical grinding, etc. The powder size D90 is less than 40μm, especially between 0.5 and 40μm, more preferably between 2 and 18μm, and can be adjusted accordingly as needed.

[0064] The binder can be any available metal powder binder, such as an organic binder. The function of the binder is to shape the metal powder particles and inject them into various complex structural parts, so that the mixture has rheological and lubricating properties after heating. The binder is a carrier that drives the powder to flow. However, the presence of organic binders will affect the performance of steel. Therefore, the requirements for the binder are: ① Small amount, using less binder can make the mixture have better rheological properties; ② Non-reactive, no chemical reaction with metal powder during the process of removing the binder; ③ Easy to remove, easy to remove in the subsequent degreasing process, and no residue in the product.

[0065] The addition ratio of stainless steel raw materials and binders depends on the actual situation. Generally, the mass ratio of stainless steel raw materials and binders is 9-11:1.

[0066] (2) Feed material preparation: the high-toughness and high-strength stainless steel raw material powder is mixed with a binder, and mixed and granulated in a plasticizing internal mixer at a temperature of 170-190°C to prepare a cylindrical metal powder feed material with a length of 3-6 mm;

[0067] (3) Injection molding: feeding the above metal powder into an injection molding machine to form a green body;

[0068] (4) Catalytic degreasing: In a special catalytic degreasing furnace for injection molding, the green body is catalytically degreased with nitric acid or oxalic acid; the temperature condition for nitric acid degreasing is 110℃±5℃, and the temperature condition for oxalic acid degreasing is 130℃±5℃;

[0069] (5) Thermal debinding and sintering: The acid-debinded green body is thermally debinded and sintered in a MIM negative pressure sintering furnace. The sintering temperature range is 1360~1380℃.

[0070] (6) Solution heat treatment: The sintered green body is heated to 1040°C-1085°C at a heating rate of 5-10°C / min in a vacuum environment, kept at this temperature for 60-120 min, and then quenched to room temperature using high-pressure gas at 6atm-10atm;

[0071] (7) Age hardening: After solution heat treatment, the samples are aged at 520~535℃ for 4~6h; or aged at 540~560℃ for 4~6h.

[0072] The steel structure is manufactured by the above method, so that the steel structure has high strength and high ductility, is not prone to breakage and deformation, and has a long service life.

[0073] In this specific embodiment, a steel structure is also provided, wherein the material used for the steel structure includes the above-mentioned steel. The material used for the steel structure includes the above-mentioned stainless steel raw material, so that the strength and toughness of the steel structure are increased, and the steel structure does not need to increase the thickness of the steel structure to further ensure the reliability of the steel structure, which is conducive to the miniaturization of the steel structure.

[0074] In this specific embodiment, the application of the above-mentioned high-toughness and high-strength stainless steel raw materials and steel structures is also provided, which are mainly used in applications in 3C products, automotive products, aviation products, medical products, etc.

[0075] 3C products usually include hardware devices such as smartphones, tablets, laptops, digital cameras, and emerging consumer electronic devices include smart wearable devices, drones, etc. It is usually used for precision and complex parts such as power interface parts, card tray camera rings, buttons, etc. in 3C products.

[0076] Some complex-shaped, bimetallic parts and grouped micro parts of automotive products are produced using the MIIM process, such as turbocharger parts, adjustment rings, fuel injector parts, blades, gearboxes, power steering components, etc.

[0077] Automotive products such as a large number of fasteners, screws, seat belt components, wing flap screw seals, micro switches, connectors, solenoids, heat sinks, optical connectors and patch panels are produced using the MIIM process.

[0078] Medical products are produced using the MIIM process, such as surgical knife handles, scissors, tweezers, dental parts, orthopedic joint parts, etc.

[0079] The above specific applications are merely examples and do not limit the protection scope of the present invention.

[0080] The invention is further described below through various embodiments.

[0081] Example 1

[0082] A high-toughness and high-strength stainless steel material composed of the following chemical elements:

[0083] Cr 7.0wt%, Ni 8.0wt%, Co 9.0wt%, Mo 6.2wt%, Nb 0.05wt%, C 0.015wt%, and the balance is Fe and inevitable impurity elements.

[0084] Example 2

[0085] A high-toughness and high-strength stainless steel material composed of the following chemical elements:

[0086] Cr 7.0wt%, Ni 7.1wt%, Co 10.3wt%, Mo 5.5wt%, Nb 0.5wt%, C 0.01wt%, and the balance is Fe and inevitable impurity elements.

[0087] Example 3

[0088] A high-toughness and high-strength stainless steel material composed of the following chemical elements:

[0089] Cr 8.5wt%, Ni 7.5wt%, Co 10.5wt%, Mo 6.0wt%, Nb 0.3wt%, C 0.012wt%, the balance is Fe and inevitable impurity elements.

[0090] Example 4

[0091] A high-toughness and high-strength stainless steel material composed of the following chemical elements:

[0092] Cr 8.5wt%, Ni 7.5wt%, Co 14.0wt%, Mo 6.5wt%, Nb 0.32wt%, C 0.01wt%, the balance is Fe and inevitable impurity elements.

[0093] Example 5

[0094] A high-toughness and high-strength stainless steel material composed of the following chemical elements:

[0095] Cr 9.0wt%, Ni 8.0wt%, Co 11.0wt%, Mo 6.6wt%, Nb 0.28wt%, C≤0.02wt%, the balance is Fe, and inevitable impurity elements.

[0096] Example 6

[0097] A high-toughness and high-strength stainless steel material composed of the following chemical elements:

[0098] Cr 8.0wt%, Ni 7.5wt%, Co 13.2wt%, Mo 6.0wt%, Nb 0.25wt%, C≤0.02wt%, the balance is Fe, and inevitable impurity elements.

[0099] Example 7

[0100] A high-toughness and high-strength stainless steel material composed of the following chemical elements:

[0101] Cr 8.0wt%, Ni 7.8wt%, Co 14.0wt%, Mo 6.4wt%, Nb 0.25wt%, C≤0.02wt%, the balance is Fe, and inevitable impurity elements.

[0102] Example 8

[0103] A high-toughness and high-strength stainless steel material composed of the following chemical elements:

[0104] Cr 7.8wt%, Ni 9.0wt%, Co 12.0wt%, Mo 7.0wt%, Nb 0.22wt%, C≤0.03wt%, the balance is Fe, and inevitable impurity elements.

[0105] Comparative Example 1

[0106] A martensitic stainless steel raw material composed of the following chemical elements:

[0107] Cr 8.5wt%, Ni 6.5wt%, Co 15.5wt%, Mo 6.0wt%, Nb 0.32wt%, C 0.005wt%, and the balance is Fe and inevitable impurity elements.

[0108] Comparative Example 2

[0109] Cr 7.0wt%, Ni 8.0wt%, Co 9.0wt%, Mo 6.0wt%, C 0.015wt%, the balance is Fe, and inevitable impurity elements.

[0110] Comparative Example 3

[0111] A stainless steel raw material composed of the following chemical elements:

[0112] Cr 6.5wt%, Ni 6.5wt%, Co 9.0wt%, Mo 6.3wt%, Nb 0.25wt%, C 0.015wt%, the balance is Fe and inevitable impurity elements.

[0113] Comparative Example 4

[0114] A stainless steel raw material composed of the following chemical elements:

[0115] Cr 7.0wt%, Ni 9.3wt%, Co 9.0wt%, Mo 5.7wt%, Nb 0.05wt%, C 0.015wt%, and the balance is Fe and inevitable impurity elements.

[0116] Comparative Example 5

[0117] A stainless steel raw material composed of the following chemical elements:

[0118] Cr 7.8wt%, Ni 9.1wt%, Co 12.0wt%, Mo7.5wt%, C 0.015wt%, Nb 0.22wt%, and the balance is Fe and inevitable impurity elements.

[0119] Example 9

[0120] A method for preparing a high-toughness and high-strength steel structure component:

[0121] (1) Raw materials preparation:

[0122] High-toughness and high-strength stainless steel raw materials and binders are prepared, and metal powder is prepared by an atomization method, and the powder has a particle size of D9530μm.

[0123] The adhesive comprises POM, EVA, PE, PP, CW and SA in a weight ratio of 78:1:4:2:2:1.

[0124] (2) Feed material preparation: The high-toughness and high-strength stainless steel raw material powder and the binder are mixed at a mass ratio of 10:1, mixed and granulated in a plasticizing internal mixer at a temperature of 170°C to prepare a cylindrical metal powder feed material with a length of 4 mm;

[0125] (3) Injection molding: The above metal powder is fed into an injection molding machine and injection molded into a test bar green body. The molding temperature is 180° C. and the molding pressure is 85 MPa.

[0126] (4) Catalytic degreasing: In a special catalytic degreasing furnace for injection molding, the green body is catalytically degreased with nitric acid; the temperature condition of nitric acid degreasing is 112°C and the degreasing time is 7 hours.

[0127] (5) Thermal debinding and sintering: The catalytically debinded green body is thermally debinded and sintered in a MIM negative pressure sintering furnace at a sintering temperature of 1375 °C and a sintering time of 5 h.

[0128] (6) Solution heat treatment: The sintered green body was heated to 1050°C at a heating rate of 8°C / min in a vacuum environment, kept at this temperature for 75 min, and then quenched to room temperature using 7atm high-pressure nitrogen gas;

[0129] (7) Aging treatment: After solution heat treatment, the samples were aged at 530 °C for 4 h to obtain steel structural parts.

[0130] Example 10

[0131] A method for preparing a high-toughness and high-strength steel structure component:

[0132] (1) Raw materials preparation:

[0133] High-toughness and high-strength stainless steel raw materials and binders are prepared, and metal powder is prepared by an atomization method, and the powder has a particle size of D9530μm.

[0134] The adhesive comprises POM, EVA, PE, PP, CW and SA in a weight ratio of 78:1:4:2:2:1.

[0135] (2) Feed material preparation: The high-toughness and high-strength stainless steel raw material powder and the binder are mixed at a mass ratio of 10:1, mixed and granulated in a plasticizing internal mixer at a temperature of 170°C to prepare a cylindrical metal powder feed material with a length of 4 mm;

[0136] (3) Injection molding: The above metal powder is fed into an injection molding machine and injection molded into a test bar green body. The molding temperature is 180° C. and the molding pressure is 85 MPa.

[0137] (4) Catalytic degreasing: In a special catalytic degreasing furnace for injection molding, the green body is catalytically degreased with nitric acid; the temperature condition of nitric acid degreasing is 112°C and the degreasing time is 7 hours.

[0138] (5) Thermal debinding and sintering: The catalytically debinded green body is thermally debinded and sintered in a MIM negative pressure sintering furnace at a sintering temperature of 1375 °C and a sintering time of 5 h.

[0139] (6) Solution heat treatment: The sintered green body was heated to 1050°C at a heating rate of 8°C / min in a vacuum environment, kept at this temperature for 75 min, and then quenched to room temperature using 7atm high-pressure nitrogen gas;

[0140] (7) Aging treatment: After solution heat treatment, the sample was aged at 550 °C for 4 h to obtain a steel structure.

[0141] The high-toughness and high-strength stainless steel raw materials of Examples 1-8 and the comparative examples were prepared by the methods of Examples 9-10, respectively. The performance test results (yield strength and elongation) of the obtained steel structures are shown in Table 1 below:

[0142]

[0143]

[0144] In summary, the stainless steel materials of the present invention in each embodiment material have excellent plasticity. Within the composition range described in the present invention, ultra-high strength and high toughness steel structures with a yield strength greater than 1900MPa and an elongation of more than 5% can be obtained. The yield strength of embodiments 3, 4, 6, and 7 is even greater than 2000MPa, and the elongation is more than 5%. The temperature of the aging treatment can also be changed to obtain a high-toughness steel structure with a yield strength greater than 1600MPa and an elongation of more than 8%. It can be applied to aerospace, medical equipment, and especially "3C" smart wearable devices, which require both high strength and high toughness.

[0145] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0146] The above is a detailed introduction to the high-toughness and high-strength stainless steel raw materials, steel structural parts, and their preparation methods and applications provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the methods of the present invention and its core ideas. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A steel structure, characterized in that: The steel structure is formed by a metal injection molding process using a high-toughness and high-strength martensitic stainless steel material, and the martensitic stainless steel material is composed of the following chemical elements: Cr 8.0~8.5wt%, Ni 7.5~8.0wt%, Co 9.5~14.0wt%, Mo 5.8~6.5wt%, Nb 0.15~0.4wt%, C≤0.03wt%, the balance is Fe, and unavoidable impurity elements; The method for preparing the steel structure comprises the following steps: S1: mixing the martensitic stainless steel material and the binder into granules to obtain a feed granule raw material; S2: injection molding the feed granular raw material into a green body; S3: catalytically debinding the green body; S4: After catalytic debinding, the green body is subjected to thermal debinding and sintering in a negative pressure environment to obtain a sintered part. The sintering temperature ranges from 1360 to 1380°C. S5: The sintered part is subjected to solution treatment and aging treatment in sequence to obtain the steel structure part; the aging treatment operation is: aging treatment is carried out at 520-535°C and heat preservation is carried out for 4-6h; the solution treatment operation is: heating to 1050°C-1085°C at a heating rate of 5-10°C / min in a vacuum environment, heat preservation is carried out for 60-120min, and then gas quenching is carried out to room temperature with 6-10atm high-pressure inert gas.

2. The steel structure according to claim 1, characterized in that: In step S1, the granulation temperature is 175-200°C.

3. The steel structure according to claim 1, characterized in that: In step S3, nitric acid or oxalic acid is used to perform catalytic degreasing on the green body; the temperature condition for nitric acid degreasing is 110°C±5°C, and the temperature condition for oxalic acid degreasing is 130°C±5°C.

4. The steel structure according to claim 1, characterized in that: The yield strength of the steel structure is 1900~2100MPa, and the elongation is 5% or more.

Citation Information

Patent Citations

  • Metal powder injection molded high-strength martensite aged steel and preparation method thereof

    CN103981436A

  • Injection molding method of high-strength and high-toughness metal part and metal rotating shaft part

    CN111250694A

  • Ultralow-carbon low-cobalt martensitic steel and preparation method thereof

    CN114480943A

  • MIM (metal injection molding) powder of 1800MPa-grade ultrahigh-strength high-toughness steel and MIM forming process of 1800MPa-grade ultrahigh-strength high-toughness steel

    CN115740427A

  • Steel, steel structural member, electronic device and preparation method for steel structural member

    WO2023025252A1